Pemberdayaan Perempuan Melalui Inklusi Keuangan dan Peningkatan Soft Skill untuk Meningkatkan Daya Saing UMKM - Maman Sulaeman; Diksi Metris; Rika Nurhidayah; Nur Azis (Fakultas Ekonomi Universitas Islam 45, 2024)
Empowering women through financial access and competency enhancement is crucial for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study examined the role of financial inclusion and soft skill improvement in empowering women involved in MSMEs. This research employed a survey method on 315 women engaged in MSMEs in Tasikmalaya, with data collection conducted using questionnaires and analysis performed using the SEM PLS method. The findings assert that financial inclusion and soft skills significantly influence the empowerment and competitiveness of MSMEs, particularly those led by women. The recommendations of this study include the need to expand financial access, provide soft skills training, and offer business support services as strategies to enhance the competitiveness of women-managed MSMEs, thereby contributing to inclusive and sustainable economic growth in Indonesia.